Inventario (arbóreo) Florístico en el Piso Altitudinal de 300 a 1400 msnm en el Bosque Siempre Verde Piemontano de la Cordillera Occidental de Los Andes - Pilatasig Sangucho, Mauro Daniel (2017)
The research has the purpose of carrying out the inventory Floristic (arboreal) in the Bosque Siempre Verde Piemontano of the Western Cordillera of the Andes in the village Los Laureles; comprising in the altitudinal floor of 300 to 1400 msnm, in this place was determined the existence of variability and floristic diversity in relation to the other altitudinal floors, a permanent plot of 6400 m 2 was drawn on this land surface, the area was limited with a rope followed with a marking tape for its better visibility in the vegetation. Inside the plot, all individual trees with a Diameter at Chest Height (DAP) equal to or greater than 10 cm were measured, collected, identified and tabulated, measured with a tape measure and then divided for the value of Pi (IIπ). This research has an important role for a decision making in the management, conservation and recovery of the forest, through research, it was known the floristic composition, the current state of the forest, the use of the species identified,mso that, based on the diagnosis, the residents of the area can have, in the short term or in the future, plans, programs and projects that allow them to change the way of life through a sustainable and sustainable management of natural resources, where man and nature are in balance. The research, shows the current state of the floristic composition of the native forest of the parish Tingo, specifically in the village the inventory, was made which is an area already intervened by man, with diverse species of the village, verifying the use value of each one of the tree species, giving an even more important importance to the place of study and to its ecosystem.